THE ROLE OF MODEL-ELICITING ACTIVITIES ON STUDENT’S MATHEMATICAL REASONING AND SELF REGULATED LEARNING - Utari Sumarmo; Suharyati Suharyati; Rippi Maya (Universitas Pendidikan Indonesia, 2019)
The study aims to analyze the role of model-eliciting activities on students’ mathematical reasoning ability and self regulated learning. This study was conducted using a pretest-post test experiment control group design. The study involved 72 eighth grade students. Instruments used were mathematical reasoning ability test, and a mathematical self regulated learning questionnaire. The study found that students who got treatment on model-eliciting activities had better grades on mathematical reasoning ability and self regulated learning than that of students taught by conventional teaching, though the students’ mathematical reasoning ability grades were at medium level and the grades of self regulated learning were at fairly good level. Students expressed positive response on Mathematics Model-eliciting Activities, even though student still realized difficulties in solving mathematical reasoning task. So we conclude that students reasoning abilities and their self-regulated learning tend to increase through model-eliciting activities